Analisis Pinjaman Sebagai Potensi Pembiayaan Pembangunan Daerah: Studi Kasus Daerah Istimewa Jogjakarta - Rokhedi Priyo Santoso (Universitas Islam Indonesia, 2003)
This research aimed to analyze the potential of regional financing from regional debt both short run and long run debt in DIY. The criterias General Revenue and Debt Service Coverage Ratio as regulated in PP 107/2000 are used to decide whether the regional government is eligible to borrow long run debt. Because all of regions are eligible according to General Revenue criteria, so the eligibility is only determined by DSCR criteria. Over period 1995 – 2002, DCSR fluctuates especially in crisis period. However, the short run eligibility criteria can not disclose the real financing needed For that reason, it is needed advance criteria that is more representative. Key word: regional debt, financing, DSCR